Impact of merit-based recruitment on the quality and efficiency of public service delivery in Nigeria - Yakubu, Ali (Faculty of Business and Economics, University of Surabaya, 2026)
Few studies have tested whether merit-based recruitment actually changes how well federal agencies in Nigeria deliver services. This study fills that gap. It asks whether merit-based recruitment raises service delivery quality and whether it improves service delivery efficiency in Nigeria's federal civil service. It also asks whether institutional capacity carries those effects, that is, whether it acts as a go-between in both relationships. A cross-sectional survey was used. Questionnaires were administered to 493 civil servants drawn from 18 federal ministries, departments, and agencies (MDAs) in Abuja. Hypotheses were tested using ordinary least squares regression through Hayes' PROCESS macro v4 for SPSS, Model 4, with 5,000 bootstrap resamples. Merit-based recruitment has a significant positive effect on institutional capacity, service delivery quality, and service delivery efficiency. Institutional capacity also has a significant positive effect on both service delivery outcomes. Institutional capacity partially mediates the relationship between merit-based recruitment and each of the two outcomes. The Federal Civil Service Commission (FCSC) and related oversight bodies in Nigeria need to apply merit-based recruitment standards more firmly and invest in building institutional capacity if they want to see real improvements in public service delivery.